Folktale 'Wendit' as the material staging the local folktale of Malang in effort to accomplish an international collaboration - Rina Wahyu Setyaningrum; Rosalin Ismayoeng Gusdian; Riski Lestiono (Universitas Muhammadiyah Malang, 2022)
This community service program focused on assisting SD Aisyiyah Kota Malang to play a virtual drama entitled ‘The Tale of Wendit' as the material staging the local folktale of Malang in effort to accomplish an international collaboration with Dajeong School Korea. The community service was carried out by sharing session about virtual drama performance, casting, rehearsals, videotaping, video launching, and virtual drama performance to teachers and students of Dajeong Primary School, Korea. Every session provided both English for Young Learners’ teachers and students opportunities to practice their reading and speaking for the performance. Besides, they also learned how to deal with digital platforms used for the rehearsal and virtual performance. The findings revealed that it was possible for teachers and students to include literature in English for Young Learners (EYL) learning in this digital era. During this pandemic, virtual drama performance can be carried out in primary school which has similar characteristics with the school where the community service was conducted.